A two-stage management strategy for the optimal operation and billing in an energy community with collective self-consumption. (15th March 2022) - Mustika, Alyssa Diva; Rigo-Mariani, Rémy; Debusschere, Vincent; Pachurka, Amaury
Abstract: This study fits in the context of collective self-consumption in energy communities, where participants within a given area can exchange and trade energy among themselves. We propose a two-stage approach that decouples the operational phase, i.e., the energy management strategy (EMS), from the settlement where the energy is contractually allocated to the participants. In particular, this decoupled approach allows testing and comparing different methods for the EMS on one side and for the energy sharing on the other, for a total of forty different investigated combinations. Rule-based and optimization-based approaches are considered, allowing each community to compare and select the most appropriate management in line with its specification. The numerical results obtained on a real test case in France show 11.7% saving on the global community bill compared to a case in which the members are not organized as a community. Also, specific allocation mechanisms proposed in this paper allow uniforming the savings in terms of individual bill reduction, which can further encourage end-users to join a community. Highlights: Four energy management strategies and ten options for energy allocation and billing. A penalization of storage systems power variations in order to incur less degradation. Community saving over 11% compared to a baseline of individual self-consumption only. Uniform members' bill reduction thanks to optimization-based benefit sharing strategy.